Method for preparing 1, 2-pentanediol through selective hydrogenolysis of furfuryl alcohol

The supported non-precious metal catalyst modified by rare earth metal oxide additives solves the problems of complex preparation process, low yield and high catalyst cost in the prior art, achieving high efficiency, stability and economical Preparation of 1,2-pentanediol.

CN119462331APending Publication Date: 2025-02-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202310948816.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art has complex reaction process, complicated post-processing, low yields when preparing 1,2-pentanediol, and high cost of preparation of precious metal catalysts, and insufficient catalyst stability and selectivity.

Method used

A supportive non-precious metal multifunctional catalyst modified with rare earth metal oxide additives was prepared by equal volume co-impregnation method, and a selective hydrogenolysis reaction of furfural/furyl alcohol was carried out in an intermittent autoclave reactor.

Benefits of technology

The efficient selective hydrogenolysis of furfuryl alcohol is achieved, the yield and selectivity of 1,2-pentanediol is improved, the catalyst preparation cost is reduced, and the catalyst has excellent stability and industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462331A_ABST
    Figure CN119462331A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing 1, 2-pentanediol through selective hydrogenolysis of furfuryl alcohol, and the method can realize directional selective fracture of C-O bonds of furfural / furfuryl alcohol and efficient preparation of 1, 2-pentanediol. According to the method, a hemicellulose downstream product furfuryl alcohol in a biomass component is directly used as a raw material and is converted into 1, 2-pentanediol with a high added value. According to the method disclosed by the invention, the conversion rate of furfuryl alcohol can be 100% on the non-noble metal Cu-based catalyst, the selectivity of 1, 2-pentanediol reaches 71.5%, and the method has extremely high stability. The catalyst is simple and convenient to prepare, low in cost and easy to recover, the product is easy to separate, and the reaction process is green and environment-friendly. The technical scheme of the invention provides a new way for preparing 1, 2-pentanediol from renewable resources which are rich in reserves, low in price and easy to obtain, and the method has excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of furfuryl alcohol catalytic conversion, and relates to a method for preparing 1,2-pentanediol by efficiently catalyzing the selective hydrogenolysis of furfuryl alcohol using a multifunctional catalyst modified with a rare earth metal oxide additive. Background Art

[0002] 1,2-Pentanediol is mainly used to prepare polyester fibers, surfactants, medicines, cosmetics and pesticide intermediates such as propiconazole. In 2019, the global 1,2-pentanediol market reached a total value of 890 million yuan, and is expected to grow to 1.3 billion yuan by 2026, with a compound annual growth rate of 5.2%. The global demand for 1,2-pentanediol is about 2,000 tons, and most of the patented preparation technologies are in the hands of multinational companies such as Ciba-Geigy. At present, there are very few domestic companies producing 1,2-pentanediol, especially almost no companies with large output, which means that the country must rely on imports to meet demand. 1,2-pentanediol products used in the field of personal care products are almost all imported, and the price is very expensive. At present, the production methods of 1,2-pentanediol mainly include the n-butanol method (Chinese patent CN201010198614.7), the n-butyraldehyde method (Chinese patent CN201110065817.3), the n-pentanoic acid method (Anhui Chemical Industry, 2002 (5): 22-23), and the n-pentene oxidation method (Chinese patent CN201410427953.6). However, the above-mentioned traditional methods for producing 1,2-pentanediol have shortcomings such as complex reaction process, cumbersome post-treatment, and low yield. Therefore, the production and preparation of 1,2-pentanediol using abundant and environmentally friendly biomass resources is considered to be a highly promising green production approach. He et al. prepared Pt / Mg(Al)O@Al2O3 for the conversion of furfuryl alcohol to produce 1,2-pentanediol. Although the yield of 1,2-pentanediol reached 85%, the catalyst preparation was complicated, and the use of precious metals greatly increased the catalyst preparation cost (ACS Catal. 2020, 10, 8032-8041). Therefore, developing a non-precious metal catalyst that is easy to prepare, has high catalytic activity and stability is crucial for the high selectivity of furfuryl alcohol to 1,2-pentanediol. Summary of the invention

[0003] The present invention proposes a method for preparing 1,2-pentanediol by selective hydrogenolysis of furfuryl alcohol, which can achieve efficient and selective cleavage of CO bonds of furfural / furfuryl alcohol, and achieve efficient preparation of 1,2-pentanediol. The prepared supported non-precious metal multifunctional catalyst not only greatly reduces the catalyst preparation cost, but also has excellent stability and 1,2-pentanediol selectivity. The method provides a non-fossil source way to prepare 1,2-pentanediol in large quantities, and has good application prospects.

[0004] A method for preparing 1,2-pentanediol by selective hydrogenolysis of furfuryl alcohol, wherein the catalyst preparation and reaction steps are as follows:

[0005] First, the magnesium oxide (MgO) carrier is calcined at 300-600°C in an air atmosphere for 0.5-6h. The composite oxide carrier is prepared by an equal volume co-impregnation method, and the preparation method is as follows: the active component M (M = Ce, La, Zn, Y) precursor solution is uniformly impregnated on 2-4g MgO carrier, preferably La. The loading amount of the metal oxide additive M is 5-20wt.% (relative to the content of the catalyst, that is, the mass of the carrier plus the metal oxide additive), preferably 5-15wt.%; then dried at 80-120°C for 8-12h, and calcined at 300-600°C in an air atmosphere for 0.5-6h, preferably 400-500°C for 3-5h, to obtain a M / MgO composite oxide carrier.

[0006] Active metal N (N = Co, Ni, Cu) is loaded on the composite carrier M / MgO, preferably Cu, by ammonia evaporation. First, the active metal N (N = Co, Ni, Cu) precursor is dissolved in 50-200 mL of water, and then 5-15 mL of concentrated ammonia water is added to adjust the pH to 9-12. After stirring at room temperature for 2-4 hours, 2-4 g of composite oxide carrier M / MgO is added. After stirring at room temperature for 4-8 hours, the temperature is raised to 80-95°C and stirred in an open air for 4-8 hours until the pH is between 7-7.5. Then filter, wash and dry the catalyst at 80-120°C for 6-12 hours. The active metal N loading is 5-20 wt.% (relative to the content of the catalyst, i.e., the mass of the composite oxide carrier plus the active metal), preferably 5-10 wt.%. The prepared catalyst is dried and ground and then calcined at 300-600°C in an air atmosphere for 0.5-6 hours, preferably 400-500°C for 3-5 hours. The obtained catalyst is then reduced under hydrogen atmosphere at 100-500°C for 1-4h, preferably at 200-300°C, and preferably for 1-2h, to finally obtain a supported multifunctional catalyst N / M / MgO. The molar ratio of active metal N to metal oxide additive M is between 1-3, preferably N / M=1-2.

[0007] The furfural / furfuryl alcohol catalytic conversion reaction is carried out in an intermittent autoclave reactor, and the operating process conditions are as follows: substrate concentration 0.5-30wt.%, preferably 0.5-5wt.%; reaction temperature 100-200°C, preferably 120-160°C; hydrogen pressure 1-6MPa, preferably 2-4MPa; reaction time 4-12h, preferably 6-10h; C2-C4 alcohol is used as solvent (ethanol / propanol / butanol), preferably isopropanol; 1,4-dioxane is used as internal standard.

[0008] Advantages of the present invention:

[0009] (1) The active metal component N in the multifunctional catalyst prepared by the present invention is highly dispersed on the carrier surface, which greatly promotes the CO cleavage step in the conversion process of furfuryl alcohol. The catalyst is simple to prepare, easy to recycle, easy to separate the product, high selectivity for 1,2-pentanediol, and the reaction process is green and environmentally friendly.

[0010] (2) Compared with the single-component N / HAP catalyst, the selectivity of 1,2-pentanediol was significantly improved after the addition of metal oxide additive M, which laid a good foundation for improving the stability of the catalyst.

[0011] (3) Compared with the currently reported literature and patents, this catalyst is easy to prepare, the cost is greatly reduced, it has an excellent 1,2-pentanediol yield, the catalyst maintains extremely high stability, and has excellent industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Transmission electron microscope images (ab) and element distribution diagram (ce) of 10Cu10La / MgO catalyst;

[0013] Figure 2 It is the stability test of furfuryl alcohol conversion catalyzed by 10Cu / 10La / MgO;

[0014] Reaction conditions: 0.2 g furfuryl alcohol, 10 mL isopropanol, 0.1 g 10Cu / 10La / MgO catalyst, reaction temperature 140°C, reaction pressure 3 MPa, reaction time 8 h; other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol. DETAILED DESCRIPTION

[0015] The specific implementation of the present invention is described in detail below in conjunction with the technical scheme and the accompanying drawings.

[0016] Example 1: Activation of MgO Support

[0017] 10 g of MgO carrier was heated from room temperature to 500° C. at a heating rate of 5° C. / min in an air atmosphere and calcined for 4 h. The white solid powder obtained after cooling was the activated MgO carrier.

[0018] Example 2: Preparation of monometallic catalyst N / MgO

[0019] Take the preparation of the monometallic catalyst 10wt.% Cu / MgO as an example (abbreviated as 10Cu / MgO): 0.6239g of copper acetate monohydrate (hereinafter referred to as copper acetate) was dissolved in 100mL of water, and then 8mL of concentrated ammonia (mass concentration 25%-28%, the same below) was added to adjust the pH to 10, stirred at room temperature for 2h, and then the MgO obtained in Example 1 was added (ensuring that the Cu content was 10wt% of the mass of the entire Cu / MgO catalyst), stirred at room temperature for 6h, and then heated to 85°C and stirred in the open for 4-8h (here 7h) until pH = 7. Then filter, wash and dry the catalyst at 100°C for 12h. Then calcine at 450°C in an air atmosphere for 3h, and after cooling, the solid powder obtained was further reduced at 200°C in a hydrogen atmosphere for 1h. After cooling, 1% O2 / N2 (volume fraction) was used for passivation for 1 hour. The obtained catalyst was recorded as 10Cu / MgO (wherein 10wt% Cu represents the content relative to the catalyst, that is, the mass of metal Cu / (mass of carrier MgO plus metal Cu) = 10wt%, and the subsequent content before the catalyst has the same meaning and will not be repeated).

[0020] Example 3: Preparation of N / M / MgO multifunctional catalyst

[0021] Take the preparation method of 10wt.%Cu / 10wt.%La / MgO as an example (abbreviated as 10Cu / 10La / MgO): 0.6230g of lanthanum nitrate hexahydrate (hereinafter referred to as lanthanum nitrate) precursor is dissolved in 100mL water and impregnated on 2.0g of MgO carrier in Example 1. The obtained composite oxide carrier is dried at 100℃ for 12h and calcined at 500℃ for 4h in air atmosphere. Then 0.6239g of copper acetate precursor is dissolved in 100mL water, 8mL of concentrated ammonia water is added to adjust the pH to 10, and La / MgO composite oxide carrier is added after stirring at room temperature for 2h (ensuring that the content of Cu and La is 10wt% and 10wt% of the total catalyst mass respectively), and the temperature is raised to 85℃ and stirred for 4-8h (in this case 7h) in the open air until pH=7. Then filter, wash and dry the catalyst at 100℃ for 12h. It was then calcined at 450°C for 3 hours in an air atmosphere, and after cooling, the solid powder obtained was further reduced at 200°C for 1 hour in a hydrogen atmosphere. After cooling, it was passivated with 1% O2 / N2 (volume fraction) for 1 hour, and the resulting catalyst was recorded as 10Cu / 10La / MgO (the numerical values ​​before the metal in the following examples have the same meaning, i.e., mass fraction; 10wt% Cu represents the content relative to the catalyst, i.e., the mass of metal Cu / (the mass of carrier MgO plus metal Cu plus metal oxide additive La) = 10wt%, 10wt% La represents the content equivalent to the entire catalyst, and the subsequent content before the catalyst has the same meaning and will not be repeated)). Figure 1It can be seen from the transmission electron microscopy and element distribution diagram that Cu and La are uniformly dispersed on the 10Cu / 10La / MgO catalytic surface, where the Cu particle size is between 0.5-2.5nm, and the La particle size is between 0.5-2.5nm, and no large agglomerated particles are formed.

[0022] As can be seen from Table 1, the MgO in Example 1 has no catalytic activity. The difference between Examples 4-7 and Comparative Examples 1-2 in Table 1 and Example 2 is that the amount of copper acetate precursor used in the catalyst preparation process by ammonia evaporation is different, which are 0.3120g (Example 4), 0.4650g (Example 5), 0.9359g (Example 6), 1.248g (Example 7), 0.1248g (Comparative Example 1) and 1.872g (Comparative Example 2), and the amount of MgO used in Examples 4-7 and Comparative Examples 1-2 is different from that in Example 2, ensuring that the Cu content is 5wt%, 7.5wt%, 15wt%, 20wt%, 2wt%, 30wt% of the entire Cu / MgO catalyst, and the remaining catalyst preparation conditions are the same as in Example 2. Taking Example 2 as an example, the catalyst was applied: 0.1g 10Cu / MgO catalyst, 0.2g furfuryl alcohol, 10mL isopropanol solvent, 0.1g internal standard 1,4-dioxane, reaction temperature 140°C, hydrogen pressure 3MPa, reaction time 8h. After the reaction is completed, the liquid product is collected by centrifugation and analyzed qualitatively and quantitatively by mass spectrometry and chromatography. The liquid products mainly include 1,2-pentanediol, 1,5-pentanediol, tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol. Among them, except for 1,2-pentanediol and 1,5-pentanediol, the remaining products are collectively referred to as others (similar to the subsequent description). From Examples 2, 4-6, and Comparative Examples 1-2 (the catalyst application process of Examples 4-6 and Comparative Examples 1-2 is consistent with the reaction conditions of the catalyst-catalyzed furfuryl alcohol conversion in Example 2, the only difference is the replacement of the catalyst), it can be seen that with the increase of Cu content, the furfuryl alcohol conversion rate continues to increase, and the selectivity of 1,2-pentanediol continues to increase. When the Cu content reaches 5wt.%, the conversion rate reaches 50.6%, and when it reaches 20wt%, the furfuryl alcohol conversion rate reaches 75.6%. Further increasing the Cu content to 30wt.%, the furfuryl alcohol conversion rate drops to 45.9%, at which time Cu is severely agglomerated (electron microscopy photos confirm that the Cu species particle size is between 5-40nm at this time), and the catalytic active sites are reduced. At the same time, with the increase of Cu content, the selectivity of 1,2-pentanediol and 1,5-pentanediol first increases and then decreases. This is because the high Cu content easily leads to the continued deoxygenation of pentanediol to form by-products such as n-pentanol. In addition, the Cu particles in the catalyst with a higher content are larger, which is more conducive to the formation of by-products tetrahydrofurfuryl alcohol, 2-methylfuran and 2-methyltetrahydrofuran. In the range of Cu content of 5-20wt%, the furfuryl alcohol conversion rate is greater than 50%, and the 1,2-pentanediol selectivity is greater than 30%, showing excellent catalytic performance. When the Cu content is 5-10wt%, the furfuryl alcohol conversion rate and 1,2-pentanediol selectivity are >50% and >30% respectively, and the Cu content is not high, which is beneficial to improve atom economy, increase the furfuryl alcohol conversion rate per unit mass of Cu, and help avoid agglomeration caused by high Cu content.Therefore, taking all factors into consideration, the Cu content is preferably in the range of 5-10 wt %, more preferably 7.5-10 wt %.

[0023] The catalyst preparation method of Examples 8-12 and Comparative Examples 3-4 in Table 1 is similar to that of Example 3, i.e., La is first impregnated and then Cu is loaded by ammonia evaporation. The difference is that the amount of lanthanum nitrate, a metal oxide additive La precursor, is different, which are 0.3115g (Example 8), 0.4673g (Example 9), 0.7788g (Example 10), 0.9345g (Example 11), 1.246g (Example 12), 0.1246g (Comparative Example 3), and 1.869g (Comparative Example 4), respectively. In addition, the amount of MgO in Examples 8-12 and Comparative Examples 3-4 is different from that in Example 3, ensuring that the Cu content is 10wt.% of the total catalyst content, and the La content is 5wt%, 7.5wt%, 12.5wt%, 15wt%, 20wt%, 2wt%, and 30wt% of the total catalyst content. The other catalyst preparation conditions are the same. The application of the catalysts in Examples 8-12 and Comparative Examples 3-4 is consistent with the reaction conditions of the 10Cu / 10La / MgO catalyst catalyzing the conversion of furfuryl alcohol in Example 3 below (the only difference is the replacement of the catalyst). Take Example 3 as an example: 0.1g 10Cu / 10La / MgO catalyst, 0.2g furfuryl alcohol, 10mL isopropanol solvent, 0.1g internal standard 1,4-dioxane, reaction temperature 140°C, hydrogen pressure 3MPa, reaction time 8h. After the reaction is completed, the liquid product is collected by centrifugation and analyzed qualitatively and quantitatively by mass spectrometry and chromatography. It can be seen from Table 1 that with the continuous increase in the content of the metal oxide additive M, the furfuryl alcohol conversion rate and the selectivity of 1,2-pentanediol continue to increase. When the metal oxide additive M=10wt%La, the furfuryl alcohol conversion rate reaches 100%, and the selectivity of 1,2-pentanediol reaches 71.5%, and the selectivity of 1,5-pentanediol reaches 20.7%. When the content of metal oxide additive La is greater than 10wt% (present in the form of LaOx, 1<x≤1.5), the furfuryl alcohol conversion rate and 1,2-pentanediol selectivity decrease. This is because the higher content of LaOx species agglomerates on the MgO surface (electron microscopy photos confirm that the particle size of La species is between 5-50nm at this time), resulting in uneven Cu dispersion and local agglomeration (electron microscopy photos confirm that the particle size of Cu species is between 5-40nm at this time), thus reducing the furfuryl alcohol conversion rate and 1,2-pentanediol selectivity. When the La content is between 5-20wt%, better furfuryl alcohol conversion rate and 1,2-pentanediol selectivity are shown. In the preferred range of La (5-15wt%), the furfuryl alcohol conversion rate is greater than 75%, and the 1,2-pentanediol selectivity is greater than 59%, with the best catalytic performance. In the more preferred range of La (7.5-15wt%), the furfuryl alcohol conversion rate is greater than 85%, and the 1,2-pentanediol selectivity is greater than 63%.

[0024] The catalyst in Comparative Example 5 is similar to the catalyst preparation in Example 3, except that in Comparative Example 3, the active metal N precursor copper acetate and the metal oxide additive M precursor lanthanum nitrate are loaded together by ammonia evaporation. The 10Cu10La / MgO-CP catalytic preparation in Comparative Example 5 is as follows: 0.6239g of copper acetate precursor and 0.6230g of lanthanum nitrate precursor are dissolved in 100mL of water, and then 8mL of concentrated ammonia water is added to adjust the pH to 10, and then MgO carrier is added after stirring at room temperature for 2h (ensuring that the content of Cu and La is 10wt% and 10wt% of the total catalyst mass, respectively), and after stirring at room temperature for 6h, the temperature is raised to 85℃ and stirred in the open for 4-8h until pH=7. The catalyst is then filtered, washed and dried at 100℃ for 12h. It is then calcined at 450℃ for 3h in an air atmosphere, and the solid powder obtained after cooling is further reduced at 200℃ for 1h in a hydrogen atmosphere. After cooling, 1% O2 / N2 (volume fraction) was used for passivation for 1 hour, and the obtained catalyst was recorded as 10Cu10La / Mg-CP. The difference between Comparative Example 6 and Example 3 is that Comparative Example 6 adopts a step-by-step impregnation method to prepare 10Cu / 10La / MgO-IM, which is as follows: 0.6230g of lanthanum nitrate precursor was dissolved in an aqueous solution and impregnated on the MgO carrier in Example 1 in equal volume. The obtained composite oxide carrier was dried at 100°C for 12 hours and calcined at 500°C for 4 hours in an air atmosphere. Then, 0.6239g of cupric acetate precursor solution was impregnated on the La / MgO composite oxide carrier in equal volume (ensuring that the Cu and La contents were 10wt% and 10wt% of the total catalyst mass, respectively). The catalyst was then dried at 100°C for 12 hours, calcined at 450°C for 3 hours in an air atmosphere, and the solid powder obtained after cooling was further reduced at 200°C for 1 hour in a hydrogen atmosphere. After cooling, 1% O2 / N2 (volume fraction) was used for passivation for 1 hour, and the obtained catalyst was recorded as 10Cu / 10La / MgO-IM. Obviously, the catalytic performance of the catalyst prepared by coprecipitation and step-by-step impregnation method is not as good as that of the catalyst prepared in Example 3 (the application process of the catalyst in Comparative Examples 5-6 is consistent with the reaction conditions of the furfuryl alcohol conversion catalyzed by the catalyst in the aforementioned Example 3, and the only difference is the replacement of the catalyst).

[0025] Table 1. Furfuryl alcohol conversion performance of N / M / MgO

[0026]

[0027]

[0028] Note: 0.2g furfuryl alcohol, 10mL isopropanol, 0.1g internal standard 1,4-dioxane, 0.1g catalyst, reaction temperature 140℃, reaction pressure 3MPa, reaction time 8h; Comparative Example 1 and Comparative Example 2 were prepared by coprecipitation and step-by-step impregnation, respectively. Other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol.

[0029] Table 2. Furfuryl alcohol conversion performance catalyzed by 10Cu / 10M / MgO

[0030]

[0031] Note: 0.2 g furfuryl alcohol, 10 mL isopropanol, 0.1 g internal standard 1,4-dioxane, 0.1 g catalyst, reaction temperature 140°C, reaction pressure 3 MPa, reaction time 8 h; other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol.

[0032] Table 2 examines the effects of different metal oxide additives on the catalytic performance of furfuryl alcohol conversion when the Cu content is constant. The catalyst preparation method of Examples 13-15 is similar to that of Example 3, that is, the metal oxide additive (Ce, Zn or Y) is first impregnated and then Cu is loaded by ammonia evaporation. The difference is that the metal oxide additive precursors are different (replacing lanthanum nitrate), respectively hexahydrated cerium nitrate, hexahydrated zinc nitrate, hexahydrated yttrium nitrate (ensuring that the content of Ce, Zn or Y is 10wt% of the total catalyst content). The reaction conditions in Examples 13-15 are consistent with the reaction conditions of the above-mentioned Example 3 catalyst catalyzing the conversion of furfuryl alcohol (the only difference is the replacement of the catalyst). Take Example 13 as an example: 0.1g 10Cu / 10Ce / MgO catalyst, 0.2g furfuryl alcohol, solvent isopropanol 10mL, internal standard 1,4-dioxane 0.1g, reaction temperature 140°C, hydrogen pressure 3MPa, reaction time 8h. After the reaction is completed, the liquid product is collected by centrifugation and analyzed qualitatively and quantitatively by mass spectrometry and chromatography. It can be seen from Table 2 that the rare earth alkali metal oxide additives Ce, La or Y have a promoting effect on the catalytic conversion of furfuryl alcohol (compared with 10Cu / MgO in Example 2), the furfuryl alcohol conversion rate is greater than 50%, and the 1,2-pentanediol selectivity is greater than 40%. This is mainly due to the adjustable 4f orbital electrons and coordination number of rare earth alkali metals. Ce, La and Y can adjust the acidity and alkalinity of the catalyst and the electronic structure, which is conducive to promoting the adsorption and activation of furfuryl alcohol and intermediates on the catalyst surface. When ZnOx is introduced as a metal oxide additive, the catalytic performance is slightly inferior to that of rare earth alkali metal oxides. Therefore, when Ce, La, Y and Zn oxides are selected as additives, they have good catalytic performance. Among them, lanthanum oxide is preferred as a metal oxide additive. At this time, the furfuryl alcohol conversion rate reaches 100%, the 1,2-pentanediol selectivity reaches 71.5%, and the total pentanediol selectivity reaches 92.2%.

[0033] The catalyst preparation method in Comparative Examples 7-9 is similar to that in Example 3, that is, the metal oxide additive (Mo, Nb or W) is first impregnated and then Cu is loaded by ammonia evaporation. The difference is that the selected metal oxide additive precursors (instead of lanthanum nitrate) are ammonium molybdate, ammonium metatungstate, and niobium chloride (ensuring that the content of Mo, Nb or W is 10wt% of the total catalyst content), and the other conditions are the same, and the application reaction conditions of the catalyst are the same as the reaction conditions of the catalyst catalyzing the furfuryl alcohol conversion in the above Example 3 (the only difference is the replacement of the catalyst). Obviously, with the introduction of acidic metal oxide additives, the selectivity of 1,2-pentanediol and 1,5-pentanediol is much lower than that of alkaline earth metals. This is mainly because the acidic metal oxide molybdenum oxide, tungsten oxide and niobium oxide can catalyze the dehydration of furfuryl alcohol and intermediates, which leads to a decrease in the selectivity of 1,2-pentanediol, and the introduction of acidic metal oxide additives will lead to substrate polymerization and a decrease in carbon balance.

[0034] Table 3. Furfuryl alcohol conversion performance of 10N / 10La / MgO

[0035]

[0036] Note: 0.2g furfuryl alcohol, 10mL isopropanol, 0.1g internal standard 1,4-dioxane, 0.1g catalyst, reaction temperature 140℃, reaction pressure 3MPa, reaction time 8h; other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol. (In Comparative Examples 6-8, the atomic ratio of the two metals is 1:1, for example, in Comparative Example 6, the atomic ratio of Cu:Ni is 1:1, and the total mass fraction is 10wt%)

[0037] Table 3 examines the effects of different types of active non-precious metal N (Co, Ni and Cu) on the catalytic performance of furfuryl alcohol conversion when the content of metal oxide additive La is constant. The catalyst preparation methods of Examples 16-17 and Comparative Examples 10-12 are similar to those of Example 3, i.e., firstly impregnating metal oxide additive LaOx (1<x≤1.5) and then loading Cu (replacing copper acetate) by ammonia evaporation, except that different types of active metals are used (cobalt nitrate, nickel nitrate, copper acetate + cobalt nitrate, copper acetate + nickel nitrate, cobalt nitrate + nickel nitrate, respectively, and the atomic ratio of the two active metals in Comparative Examples 10-12 is 1:1) (ensuring that the active metal content is 10wt% of the total catalyst mass), and the other conditions are the same; and the application reaction conditions of the catalyst are the same as the reaction conditions of the catalyst catalyzing furfuryl alcohol conversion in the above Example 3 (the only difference is the replacement of the catalyst). Take Example 16 as an example: 0.1g 10Co / 10La / MgO catalyst, 0.2g furfuryl alcohol, 10mL isopropanol solvent, 0.1g internal standard 1,4-dioxane, reaction temperature 140°C, hydrogen pressure 3MPa, reaction time 8h. After the reaction is completed, the liquid product is collected by centrifugation and analyzed qualitatively and quantitatively by mass spectrometry and chromatography. It can be seen from Table 3 that the active metals Cu, Ni and Co are beneficial to promoting the conversion of furfuryl alcohol, with a conversion rate of 100%, and the selectivity of pentanediol is greater than 26%, which has good catalytic activity. Since Co and Ni are more prone to hydrogenation reactions, the by-product tetrahydrofurfuryl alcohol becomes the main product. In Comparative Examples 10-12, the conversion rate of furfuryl alcohol on the bimetallic catalyst is as high as 100%, but the selectivity of 1,2-pentanediol is less than 20%. This result shows that the metal Cu has suitable hydrogenation and hydrogenolysis activity, which is beneficial to avoid the formation of excessive hydrogenation and hydrogenolysis products, so Cu is preferred as the active metal.

[0038] Table 4. Effect of support on catalytic performance of furfuryl alcohol conversion

[0039]

[0040] Note: 0.2 g furfuryl alcohol, 10 mL isopropanol, 0.1 g internal standard 1,4-dioxane, 0.1 g catalyst, reaction temperature 140°C, reaction pressure 3 MPa, reaction time 8 h; other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol.

[0041] After determining the best metal oxide additive and active metal, the effect of the carrier on the catalytic conversion performance of furfuryl alcohol was further investigated, as shown in Table 4. The catalyst preparation method and reaction conditions in Comparative Examples 13-17 are similar to those in Example 3, that is, La is first impregnated on the carrier and then Cu is loaded by ammonia evaporation. The difference is that the selected carriers are Al2O3, SiO2, TiO2, ZrO2 and CeO2 of the same mass (ensuring that the content of Cu and La is 10wt% and 10wt% of the entire catalyst) respectively, and the other conditions are the same. And the application reaction conditions of the catalyst are consistent with the reaction conditions of the catalyst catalyzing the conversion of furfuryl alcohol in the above-mentioned Example 3 (the only difference is the replacement of the catalyst); Take Comparative Example 13 as an example: 0.1g 10Cu / 10La / Al2O3 catalyst, 0.2g furfuryl alcohol, solvent isopropanol 10mL, internal standard 1,4-dioxane 0.1g, reaction temperature 140℃, hydrogen pressure 3MPa, reaction time 8h. After the reaction is completed, the liquid product is collected by centrifugation and analyzed qualitatively and quantitatively by mass spectrometry and chromatography respectively. It can be clearly seen from Table 4 that when acidic carriers such as Al2O3, TiO2, and ZrO2 are selected, the furfuryl alcohol conversion rates are 75.6%, 62.6%, and 49.8%, respectively, and the selectivity of 1,2-pentanediol is less than 20%. At this time, the selectivity of 1,5-pentanediol is higher than that of 1,2-pentanediol. This shows that the acidic carrier is conducive to the formation of 1,5-pentanediol, and there are more side reactions on the acidic carrier. The selectivity of other products is as high as 45.5%, 58.4%, and 64.2%, respectively (other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran, and n-pentanol). In Comparative Example 17, when the alkaline metal oxide CeO2 is used as the carrier, the conversion rate is 49.8%, and the selectivity of 1,2-pentanediol is 24.6%. This is mainly due to the low specific surface area of ​​CeO2, which leads to low dispersion of active metals, and thus poor catalytic performance. Therefore, the best furfuryl alcohol conversion and 1,2-pentanediol selectivity were achieved when basic metal oxide MgO was used as the support.

[0042] Table 5. Effect of reaction temperature on catalytic furfuryl alcohol conversion performance

[0043]

[0044] Note: 0.2 g furfuryl alcohol, 10 mL isopropanol, 0.1 g internal standard 1,4-dioxane, 0.1 g 10Cu / 10La / MgO catalyst, reaction pressure 3 MPa, reaction time 8 h; other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol.

[0045] Table 5 examines the effect of reaction temperature on the catalytic conversion performance of furfuryl alcohol. The catalysts used in Examples 18-22 and Comparative Examples 18-19 are all 10Cu / 10La / MgO in Example 3. The catalyst catalyzes the conversion of furfuryl alcohol under similar conditions to those in Example 3, except that the reaction temperature is different, which is 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 80°C, and 220°C, respectively. The other conditions are the same. Take Example 18 as an example: 0.1g 10Cu / 10La / MgO catalyst, 0.2g furfuryl alcohol, 10mL isopropanol solvent, 0.1g internal standard 1,4-dioxane, 100°C reaction temperature, 3MPa hydrogen pressure, and 8h reaction time. After the reaction is completed, the liquid product is collected by centrifugation and analyzed qualitatively and quantitatively by mass spectrometry and chromatography, respectively. As shown in Table 5, the reaction temperature has a significant effect on the conversion performance of furfuryl alcohol. As the reaction temperature increases, the furfuryl alcohol conversion rate gradually increases. When the reaction temperature reaches 120°C, the furfuryl alcohol conversion rate reaches 82.9%, and the 1,2-pentanediol selectivity is also close to 60%. When the reaction temperature reaches 140°C, the 1,2-pentanediol selectivity is the highest, reaching 71.5%, and the 1,5-pentanediol selectivity is 20.7%, and the total pentanediol selectivity is as high as 92.2%. Further increasing the reaction temperature, the selectivity of 1,2-pentanediol and 1,5-pentanediol gradually decreases, and the over-hydrogenation product dominates at this time. Therefore, within the temperature range of 100-200°C, it has good catalytic performance. Among them, within the temperature range of 120-160°C, the furfuryl alcohol conversion rate is greater than 82%, and the 1,2-pentanediol selectivity is greater than 59%. Within the range of 140-160°C, the furfuryl alcohol conversion rate reaches 100%, and the 1,2-pentanediol selectivity is greater than 65%, which has the best catalytic activity.

[0046] Table 6. Effect of hydrogen pressure on catalytic furfuryl alcohol conversion performance

[0047]

[0048] Note: 0.2 g furfuryl alcohol, 10 mL isopropanol, 0.1 g internal standard 1,4-dioxane, 0.1 g 10Cu / 10La / MgO catalyst, reaction temperature 140°C, reaction time 8 h; other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol.

[0049] Hydrogen pressure is also one of the important parameters affecting reaction performance. The effect of hydrogen pressure on the conversion performance of furfuryl alcohol is investigated in Table 6. The catalysts used in Examples 23-27 and Comparative Examples 20-21 are all 10Cu / 10La / MgO in Example 3. The reaction conditions for the catalytic conversion of furfuryl alcohol are similar to those in Example 3, except that the reaction hydrogen pressures are different, which are 1MPa, 2MPa, 3MPa, 4MPa, 5MPa, 6MPa, 0.1MPa, and 8MPa, respectively, and the other conditions are the same. Take Example 23 as an example: 0.1g 10Cu / 10La / MgO catalyst, 0.2g furfuryl alcohol, solvent isopropanol 10mL, internal standard 1,4-dioxane 0.1g, reaction temperature 140°C, hydrogen pressure 1MPa, and reaction time 8h. After the reaction is completed, the liquid product is collected by centrifugation and analyzed qualitatively and quantitatively by mass spectrometry and chromatography. From Table 6, it can be seen that when the hydrogen pressure in Comparative Example 20 is 0.1MPa, the furfuryl alcohol conversion rate is only 21.5%, and the 1,2-pentanediol selectivity is only 15.6%. When the hydrogen pressure is 1MPa, the furfuryl alcohol conversion rate rises rapidly to 63.7%. Further increasing the hydrogen pressure, the furfuryl alcohol conversion rate reaches 83.2% at 2MPa, and the 1,2-pentanediol selectivity reaches 62.3% at this time. When the hydrogen pressure is greater than 3MPa, the selectivity of 1,2-pentanediol and 1,5-pentanediol gradually decreases, which means that the over-hydrogenation products dominate. When the hydrogen pressure is 8MPa, the by-product selectivity is as high as 73.7%, and the main products are 2-methylfuran, 2-methyltetrahydrofuran and tetrahydrofuran. In the range of 1-6MPa hydrogen pressure, it has a good furfuryl alcohol conversion rate and 1,2-pentanediol selectivity. In the pressure range of 2-4 MPa, furfuryl alcohol can maintain a 100% conversion rate while the selectivity of 1,2-pentanediol is higher than 65%. In the hydrogen pressure range of 3-4 MPa, the catalytic activity is the best, the furfuryl alcohol conversion rate reaches 100%, and the selectivity of 1,2-pentanediol is greater than 65%.

[0050] Table 7. Effect of reaction time on catalytic furfuryl alcohol conversion performance

[0051]

[0052]

[0053] Note: 0.2 g furfuryl alcohol, 10 mL isopropanol, 0.1 g internal standard 1,4-dioxane, 0.1 g 10Cu / 10La / MgO catalyst, reaction temperature 140°C, reaction pressure 3 MPa; other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol.

[0054] Table 7 examines the effect of reaction time on the catalytic conversion performance of furfuryl alcohol. The catalysts used in Examples 28-31 and Comparative Examples 22-25 are all 10Cu / 10La / MgO in Example 3. The catalyst-catalyzed furfuryl alcohol conversion reaction conditions are similar to those in Example 3, except that the reaction time is different, which are 4h, 6h, 10h, 12h, 0.5h, 1h, 2h, and 16h, respectively, and the other conditions are the same. Take Example 28 as an example: 0.1g 10Cu / 10La / MgO catalyst, 0.2g furfuryl alcohol, 10mL isopropanol solvent, 0.1g internal standard 1,4-dioxane, reaction temperature 140°C, hydrogen pressure 3MPa, reaction time 4h. After the reaction is completed, the liquid product is collected by centrifugation and analyzed qualitatively and quantitatively by mass spectrometry and chromatography, respectively. It can be seen from Table 7 that when the reaction time is 0.5-2h, the furfuryl alcohol conversion rate is less than 40%, and the 1,2-pentanediol selectivity is 30.5%. As the reaction time increases, the furfuryl alcohol conversion rate and 1,2-pentanediol selectivity gradually increase. When the reaction time exceeds 8h, although the conversion rate reaches 100%, the selectivity of 1,2-pentanediol and 1,5-pentanediol decreases, and an overhydrogenolysis reaction occurs at this time, and pentanediol is hydrogenolyzed to produce n-pentanol. In comparative example 25, when the reaction time is 16h, the selectivity of 1,2-pentanediol is only 12.5% ​​and the selectivity of 1,5-pentanediol is 1.5%. Within 4-12h of reaction, the furfuryl alcohol conversion rate is greater than 80%, and the selectivity of 1,2-pentanediol is greater than 54%. Further, within 6-10h, the furfuryl alcohol conversion rate is greater than 90%, and the selectivity of 1,2-pentanediol is greater than 64%. When the reaction time is 8-10h, it has the best catalytic activity, the furfuryl alcohol conversion rate reaches 100%, and the selectivity of 1,2-pentanediol is greater than 64%.

[0055] Table 8. Effect of furfuryl alcohol concentration on catalytic furfuryl alcohol conversion performance

[0056]

[0057] Note: 10mL isopropanol, 0.1g internal standard 1,4-dioxane, 10Cu / 10La / MgO catalyst (the mass of the catalyst is 50% of the mass of furfuryl alcohol), reaction temperature 140℃, reaction pressure 3MPa; other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol.

[0058] Table 8 examines the effect of furfuryl alcohol concentration on catalytic conversion performance. The catalysts used in Examples 32-37 and Comparative Example 26 are consistent with Example 3, all of which are 10Cu / 10La / MgO, and the catalyst-catalyzed furfuryl alcohol conversion reaction conditions are similar to those of Example 3 above, except that the furfuryl alcohol concentrations are different, 0.5wt%, 1wt%, 2.5wt%, 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, respectively, and the other conditions are consistent. Take Example 33 as an example: 0.1g 10Cu / 10La / MgO catalyst, 0.08g furfuryl alcohol, 10mL isopropanol solvent, 0.1g internal standard 1,4-dioxane, reaction temperature 140°C, hydrogen pressure 3MPa, reaction time 8h. After the reaction is completed, the liquid product is collected by centrifugation and analyzed qualitatively and quantitatively by mass spectrometry and chromatography, respectively. When the furfuryl alcohol concentration is between 0.5-30wt%, the furfuryl alcohol conversion rate and 1,2-pentanediol selectivity are better. In the reaction of low concentration furfuryl alcohol (0.5-5wt%), the furfuryl alcohol conversion rate is greater than 95%, and the 1,2-pentanediol selectivity is greater than 62%. Obviously, when the furfuryl alcohol concentration is between 0.5-2.5wt%, it has the best catalytic activity, the furfuryl alcohol conversion rate reaches 100%, and the 1,2-pentanediol selectivity is greater than 62%. Further increasing the furfuryl alcohol concentration, the conversion rate and selectivity decrease at the same time. This is mainly due to the fact that the substrate in the high concentration furfuryl alcohol solution is prone to polymerization, resulting in the adsorption of polymers on the catalyst surface, reducing the catalytic active sites, and thus the catalytic performance is inhibited, and the carbon balance in the high concentration furfuryl alcohol solution is poor.

[0059] Table 9. Effect of solvent on catalytic furfuryl alcohol conversion performance

[0060]

[0061] Note: 0.2g furfuryl alcohol, 0.1g internal standard 1,4-dioxane, 0.1g 10Cu / 10La / MgO catalyst, reaction temperature 140℃, reaction pressure 3MPa; other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol.

[0062] Table 9 investigates the effect of reaction solvent on the catalytic conversion performance of furfuryl alcohol. The catalysts used in Examples 38-40 and Comparative Examples 27-29 are all 10Cu / 10La / MgO in Example 3, and the catalyst catalyzes the furfuryl alcohol conversion reaction conditions similar to those in Example 3 above, except that the selected solvents are different, namely ethanol, n-propanol, n-butanol, methanol, water, and n-decane (ensuring that the mass content of furfuryl alcohol is 2.5wt%), and the other conditions are the same. Take Example 38 as an example: 0.1g 10Cu / 10La / MgO catalyst, 0.2g furfuryl alcohol, 10mL solvent ethanol, 0.1g internal standard 1,4-dioxane, reaction temperature 140°C, hydrogen pressure 3MPa, and reaction time 8h. After the reaction is completed, the liquid product is collected by centrifugation and analyzed qualitatively and quantitatively by mass spectrometry and chromatography, respectively. When C2-C4 alcohol is used as a solvent, the furfuryl alcohol conversion rate and 1,2-pentanediol selectivity increase with the increase of carbon number. Among them, isopropanol has the best catalytic performance when used as solvent, which is due to its excellent hydrogen transfer ability. When water is used as solvent, the conversion rate is only 23.5%, because in the aqueous phase, furfuryl alcohol is severely polymerized, and the intermediate product undergoes a rearrangement reaction to generate cyclopentanone and cyclopentanol, rather than pentanediol. When non-polar solvent n-decane is used as solvent, there is basically no conversion. Therefore, it is beneficial to promote the occurrence of the reaction when an alcohol that can undergo hydrogen transfer is selected as a solvent, and isopropanol is preferably used as a solvent.

[0063] Table 10. Effect of catalyst calcination temperature on catalytic furfuryl alcohol conversion performance

[0064]

[0065] Note: 0.2 g furfuryl alcohol, 10 mL isopropanol, 0.1 g internal standard 1,4-dioxane, 0.1 g 10Cu / 10La / MgO catalyst, reaction temperature 140°C, reaction pressure 3 MPa, reaction time 8 h; other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol.

[0066] Table 10 examines the effect of catalyst calcination temperature on the conversion performance of furfuryl alcohol. The catalysts used in Examples 41-44 and Comparative Examples 30-31 and Example 3 are all 10Cu / 10La / MgO. The difference from the catalyst used in Example 3 is that the catalyst calcination temperatures are different, namely 300°C, 400°C, 500°C, 600°C, 200°C, and 700°C, respectively, and the other conditions are the same; and the catalyst catalytic furfuryl alcohol conversion reaction conditions are the same as those in Example 3 above (the only difference is the replacement of the catalyst). Take Example 42 as an example: 0.1g 10Cu / 10La / MgO catalyst was calcined at 400°C for 3h, 0.2g furfuryl alcohol, 10mL of isopropanol solvent, 0.1g of internal standard 1,4-dioxane, reaction temperature of 140°C, hydrogen pressure of 3MPa, and reaction time of 8h. After the reaction is completed, the liquid product is collected by centrifugation and analyzed qualitatively and quantitatively by mass spectrometry and chromatography, respectively. Obviously, as the catalyst calcination temperature increases, the furfuryl alcohol conversion rate and 1,2-pentanediol selectivity gradually increase. In the calcination temperature range of 300-600℃, the furfuryl alcohol conversion rate and 1,2-pentanediol selectivity are greater than 66% and 45%, respectively. In the calcination temperature range of 400-500℃, the furfuryl alcohol conversion rate is greater than 95%, and the 1,2-pentanediol selectivity is greater than 64%, with the best catalytic activity. Further increasing the catalyst calcination temperature, the catalytic performance decreases rapidly, which is mainly due to the serious agglomeration of Cu species at high temperature (semiconductor microscopy results confirm that the Cu particle size is between 5-40nm at this time), so the number of catalytic active sites decreases significantly, which is not conducive to the occurrence of the reaction.

[0067] Table 11. Effect of catalyst reduction temperature on catalytic furfuryl alcohol conversion performance

[0068]

[0069]

[0070] Note: 0.2 g furfuryl alcohol, 10 mL isopropanol, 0.1 g internal standard 1,4-dioxane, 0.1 g 10Cu / 10La / MgO catalyst, reaction temperature 140°C, reaction pressure 3 MPa, reaction time 8 h; other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol.

[0071] Catalyst reduction temperature is also one of the important factors affecting catalyst performance. The catalysts used in Examples 45-48 and Comparative Examples 32-33 in Table 11 are all 10Cu / 10La / MgO, which is different from the catalyst used in Example 3 in that the catalyst reduction temperature is different, which is 100°C, 300°C, 400°C, 500°C, 50°C, and 600°C, respectively, and the other conditions are the same; and the catalyst catalytic furfuryl alcohol conversion reaction conditions are the same as those in the above-mentioned Example 3 (the only difference is the replacement of the catalyst). Take Example 45 as an example: 0.1g 10Cu / 10La / MgO catalyst is calcined at 450°C for 3h and then reduced at 100°C for 1h, 0.2g furfuryl alcohol, 10mL solvent isopropanol, 0.1g internal standard 1,4-dioxane, reaction temperature 140°C, hydrogen pressure 3MPa, reaction time 8h. After the reaction is completed, the liquid product is collected by centrifugation and analyzed qualitatively and quantitatively by mass spectrometry and chromatography. When the reduction temperature is low, taking comparative example 32 as an example, at this time, the Cu species mainly exists in the form of CuO, and the ability to dissociate hydrogen is weak, making it difficult to promote hydrogenation and hydrogenolysis reactions. As the reduction temperature increases, the furfuryl alcohol conversion rate and 1,2-pentanediol selectivity increase. When the reduction temperature is between 100-500°C, the furfuryl alcohol conversion rate is greater than 64%, and the 1,2-pentanediol selectivity is greater than 31%, which has good catalytic activity. When the reduction temperature is between 200-300°C, the furfuryl alcohol conversion rate and 1,2-pentanediol selectivity reach 100% and greater than 66%, respectively, with optimal catalytic activity. Further increasing the reduction temperature, CuO is over-reduced, and zero-valent Cu species dominates, so the number of over-hydrogenation by-products increases. At the same time, a higher reduction temperature is also conducive to Cu agglomeration (electron microscopy results confirm that the Cu particle size is between 5-40nm at this time), reducing the dispersion, which is not conducive to the conversion of furfuryl alcohol.

[0072] Table 12. Effect of Cu and La atomic ratio on catalytic performance of furfuryl alcohol conversion

[0073]

[0074] Note: 0.2 g furfuryl alcohol, 10 mL isopropanol, 0.1 g internal standard 1,4-dioxane, 0.1 g catalyst, reaction temperature 140°C, reaction pressure 3 MPa, reaction time 8 h; other products mainly include tetrahydrofurfuryl alcohol, 2-methylfuran, 2-methyltetrahydrofuran and n-pentanol.

[0075] In addition to the absolute contents of Cu and La, the ratio between Cu and La is also crucial for the catalytic conversion performance of furfuryl alcohol (taking the absolute content of La as 10wt% as an example), as shown in Table 12. The catalysts used in Examples 49-51 and Comparative Examples 34-37 are similar to those in Example 3, that is, firstly impregnating La and then loading Cu by ammonia evaporation, except that the amounts of Cu and La precursors are different, and the atomic ratios of Cu and La are Cu:La=1, 1.5, 3, 4, 0.5, 4, 5, 10, respectively, and the other conditions are consistent with those in the above-mentioned Example 3; and the reaction conditions for the catalytic conversion of furfuryl alcohol are consistent with those in the above-mentioned Example 3 (the only difference is the replacement of the catalyst). Take Comparative Example 34 as an example: 0.1g 2Cu / 10La / MgO catalyst, 0.2g furfuryl alcohol, 10mL isopropanol solvent, 0.1g internal standard 1,4-dioxane, reaction temperature 140°C, hydrogen pressure 1MPa, reaction time 8h. After the reaction is completed, the liquid product is collected by centrifugation and analyzed qualitatively and quantitatively by mass spectrometry and chromatography, respectively. When Cu:La is low, taking comparative example 34 as an example, at this time, the Cu content is low and the La content is high, and part of the Cu is covered by La species, resulting in low catalytic activity. Obviously, when Cu:La=1-3, the furfuryl alcohol conversion is greater than 80%, and the 1,2-pentanediol selectivity is greater than 50%. When Cu:La=1-2, the furfuryl alcohol conversion is greater than 80%, and the 1,2-pentanediol selectivity is greater than 62%. When Cu:La=1.5-2, it has the best catalytic activity, the furfuryl alcohol conversion is greater than 90%, and the 1,2-pentanediol selectivity is greater than 66%. Increasing the Cu:La ratio is conducive to the formation of over-hydrogenation products, thereby resulting in a decrease in the target 1,2-pentanediol selectivity.

[0076] Example 52 is a stability test of the conversion of furfuryl alcohol catalyzed by the catalyst 10Cu / 10La / MgO used in Example 3. The specific operating steps are as follows: 0.2g furfuryl alcohol, 10mL isopropanol, 0.1g internal standard 1,4-dioxane, 0.1g 10Cu / 10La / MgO catalyst, reaction temperature 140°C, reaction pressure 3MPa, reaction time 8h. After each reaction, the catalyst was centrifuged and washed with isopropanol 3 times and then dried (80°C) for 6h, and then added to the reactor, and 0.2g furfuryl alcohol and 10mL isopropanol were added, 3MPa hydrogen was filled in, and the temperature was raised to 140°C for the next cycle reaction. The liquid product after each reaction was centrifuged and then qualitatively analyzed by mass spectrometry and quantitatively analyzed by gas chromatography. The reaction results are shown in Figure 2 It can be seen from the figure that the substrate conversion rate and 1,2-pentanediol selectivity of the 10Cu / 10La / MgO catalyst prepared by the present invention remain basically unchanged in 6 cycles, the conversion rate is maintained at 100%, and the 1,2-pentanediol selectivity is maintained at about 71%, indicating that the catalyst has excellent stability and has good industrial application prospects.

Claims

1. A method for preparing 1,2-pentanediol by selective hydrogenolysis of furfuryl alcohol, characterized in that: The catalyst used is abbreviated as N / M / S, where N is the active metal, M is the metal oxide additive, and S is the catalyst carrier magnesium oxide (MgO); The active metal N and the metal oxide additive M are uniformly dispersed on the surface of the carrier, the active metal N is one or more of non-precious metals such as Cu, Ni, Co, etc., preferably Cu, and the content of active metal N is 5-20wt% of the total mass of the catalyst (the sum of the mass of N, M and the carrier S), preferably 5-10wt%, and more preferably 7.5-10wt%; M is one or two of Ce, La, Zn and Y metal oxides, preferably La, and the content of the additive M is 5-20wt% of the total mass of the catalyst (the sum of the mass of N, M and the carrier S), preferably 5-15wt%, and more preferably 7.5-15wt%.

2. The method according to claim 1, characterized in that: The active metal N and the metal oxide additive M are uniformly dispersed on the surface of the carrier MgO, and the particle size of the active metal N is between 0.5-2.5 nm.

3. The method according to claim 1 or 2, characterized in that: The required catalyst preparation method is a two-step process of impregnation followed by ammonia evaporation: First, a composite oxide support is prepared by an equal volume or excess volume co-impregnation method, and the preparation method is as follows: a precursor solution of an active component M (M = one or more of Ce, La, Zn, and Y) is uniformly impregnated on a MgO support in an equal volume or excess volume, and the loading amount of the metal oxide additive M is 2-20wt.% (relative to the total final catalyst mass), preferably 5-10wt.%; then, drying at 80-120° C. for 8-12h, and calcining at 300-600° C. for 0.5-6h (preferably 400-500° C. for 3-5h) in an air atmosphere to obtain a M / MgO composite oxide support; Active metal N (N = Co, Ni, Cu) is loaded on the composite carrier M / MgO; first, the active metal N (N = one or more of Co, Ni, Cu) precursor is dissolved in water, and then concentrated ammonia is added to adjust the pH to 9-12, and then the composite oxide carrier M / MgO is added after stirring at room temperature for 2-4 hours, and then the temperature is raised to 80-95°C and stirred in an open container for 4-8 hours until the pH is between 7.0-7.5; then the catalyst is filtered, washed and dried at 80-120°C for 6-1 2h; the active metal N loading is 2-20wt.% (relative to the total final catalyst mass), preferably 5-10wt.%; the prepared catalyst is dried and ground and then calcined at 300-600°C in an air atmosphere for 0.5-6h (preferably 400-500°C for 3-5h); the obtained catalyst is then reduced at 100-500°C in a hydrogen atmosphere for 1-4h (preferably the reduction temperature is 200-300°C, and the preferred reduction time is 1-2h) to finally obtain a supported multifunctional catalyst N / M / MgO.

4. The method according to claim 3, characterized in that: The selected N precursor is one or more of the acetates or nitrates corresponding to the active metal N; the selected auxiliary agent M precursor is one or more of the chlorides or nitrates corresponding to the auxiliary agent M.

5. The method according to claim 1, characterized in that: The reaction is carried out in an intermittent autoclave reactor, and the operating process conditions are: substrate concentration 0.5-30wt.%, preferably 0.5-5wt.%, more preferably 0.5-2.5wt%; reaction temperature 100-200°C, preferably 120-160°C, more preferably 140-160°C; hydrogen pressure 1-6MPa, preferably 2-4MPa, more preferably 3-4MPa; reaction time 4-12h, preferably 6-10h, more preferably 8-10h; C2-C4 alcohol is used as solvent (ethanol, propanol, butanol), preferably isopropanol.

6. The method according to claim 5, characterized in that: 1,4-Dioxane was used as the internal standard.

7. The method according to claim 1, 2 or 3, characterized in that: The molar ratio of the active metal N to the metal oxide additive M is between 1-3, preferably N / M=1-2, more preferably N / M=1.5-2.

Citation Information

Patent Citations

  • Method for synthesizing 1,2-pentanediol from n-butyl alcohol

    CN101857524A

  • Method for synthesizing 1,2-pentanediol

    CN102180769B

  • Preparation of 1,2-pentanediol through oxidative hydrolysis of alpha-amylene

    CN105461511A

Cited By

  • Supported catalyst, preparation method thereof and application of supported catalyst in continuous production of pentanediol in fixed bed

    CN122273515A